Pengaruh Struktur Kepemilikan Keluarga Terhadap Kinerja Perusahaan pada Perusahaan Sektor Pertanian - Lisa Lisa Lisa; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This study aimed to identify and to prove the existence of a relationship between the high affect of family ownership toward an increasing in the firm performance as measured by using return on asset (ROA). Family ownership measured by using the value of 1 or 0, seen from the shares owned by the family in the company or whether there is a family which contributes in managerial position in the company. Firm performance measured by ROA from the net income after interest and tax divided by the total asset. This study used control variables of good coroporate governance and firm size. The research was conducted on go public companies of agriculture sector listed in BEI with a sample of 51 observations. The results showed that there was influence of family ownership on firm performance. The results also showed that good corporate governance and firm size had no significant affect towards firm performance.